2019
DOI: 10.1111/sode.12425
|View full text |Cite
|
Sign up to set email alerts
|

What you say, and how you say it: Preschoolers' growth in vocabulary and communication skills differentially predict kindergarten academic achievement and self‐regulation

Abstract: The idea that language skills support school readiness, predicting later self‐regulation and academic success, is widely accepted. Although vocabulary is often emphasized in the developmental literature, the ability to use language appropriately in the classroom, or social communication skills, may also be critical. This article examined longitudinal contributions of children's vocabulary and social communication skills, from preschool to kindergarten, to kindergarten academic achievement (reading and math) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
0
25
0
1
Order By: Relevance
“…In all tests, we controlled for expressive and receptive vocabulary development, and family SES. Early vocabulary predicts later social skills (Izard et al, 2001 ; Mostow et al, 2002 ) and school achievement (Ramsook et al 2019 ), for children in both low‐ and middle‐income families (Ackerman et al, 2003 ). Language skills also predict false‐belief task performance, and moderate relations between false‐belief performance and social competence (Astington, 2003 ; Astington & Jenkins, 1999 ; DeRosney & Hughes, 2006 ; de Villiers & de Villiers, 2000 ; de Villiers & Pyers, 2002 ; Hale & Tager‐Flusberg, 2003 ; Jenkins & Astington, 1996 ; Watson et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In all tests, we controlled for expressive and receptive vocabulary development, and family SES. Early vocabulary predicts later social skills (Izard et al, 2001 ; Mostow et al, 2002 ) and school achievement (Ramsook et al 2019 ), for children in both low‐ and middle‐income families (Ackerman et al, 2003 ). Language skills also predict false‐belief task performance, and moderate relations between false‐belief performance and social competence (Astington, 2003 ; Astington & Jenkins, 1999 ; DeRosney & Hughes, 2006 ; de Villiers & de Villiers, 2000 ; de Villiers & Pyers, 2002 ; Hale & Tager‐Flusberg, 2003 ; Jenkins & Astington, 1996 ; Watson et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual print knowledge has been minimally explored in children with hearing loss specifically, but it has been well documented for children with normal hearing. Many studies of children with normal hearing have found significant positive correlations between measures of conceptual print knowledge and vocabulary, indicating that children with larger vocabularies are more likely to score well on print knowledge measures than children with smaller vocabularies (Dickinson et al, 2003;Dickinson & Snow, 1987;Ramsook et al, 2019). Justice et al (2010) similarly found that initial language ability moderated effects of intervention on conceptual print knowledge gains.…”
Section: Conceptual Vocabulary Knowledgementioning
confidence: 95%
“…It is possible that, for children with hearing loss and with normal hearing, delays in conceptual print knowledge are exacerbated by delays in vocabulary (e.g., Dickinson et al, 2003;Dickinson & Snow, 1987;Justice et al, 2010;Ramsook et al, 2019). Conceptual print knowledge has been minimally explored in children with hearing loss specifically, but it has been well documented for children with normal hearing.…”
Section: Conceptual Vocabulary Knowledgementioning
confidence: 99%
“…Toddlerhood is a period of both pronounced growth in language abilities and more complex forms of parent–child interaction (Harrist & Waugh, 2002; Huttenlocher et al, 2010), making this a prime developmental period to examine the role of maternal depression in child language development. In addition, children begin to enter formal schooling around the age of 5, and language skills are a key indicator of school readiness and have been tied to future academic success (Heaviside & Farris, 1993; Ramsook et al, 2020).…”
Section: Maternal Depression and Child Language Developmentmentioning
confidence: 99%